Bacteria in drinking water - Duehn, Carl O. (My University, 1904)
Introduction: Pure drinking water is a requisite of good health. Therefore the condition of our drinking water should interest us all. Although bacteria are found most everywhere in external nature, water is one of the best media for the transferance of bacteria. It is of hygienic and economic importance that we know about the condition of our drinking water. The bacteria in drinking water are of economic importance because the health of a community depends upon the water which the people drink. Polluted water is usually the source of contaminating of such diseases as typhoid fever end Asiatic cholera. The bacteria which may be found in a certain water supply is not only of importance to the bacteriologist but is of the greatest importance to practical hygiene. There has been outbreaks of typhoid. fever in recent years caused by contaminated water. One example of an outbreak of typhoid fever was at Ithaca, New York in 1902.
Citation: Duehn, Carl O. Bacteria in drinking water. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Drinking Water; Bacteria; Sanitation; Water; Theses